Analisis Tingkat Pengetahuan Masyarakat Terhadap Penyakit dan Vaksin Hepatitis A di Indonesia: Analysis of Community’s Knowledge on Hepatitis A Disease and Vaccines in Indonesia - Ahmad, Irfan; Endarti, Dwi; Andayani, Tri Murti (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2020)
Hepatitis A is a viral disease with a high potential for morbidity and mortality. It is also the second highest viral disease in Indonesia after hepatitis B. Community’s knowledge regarding Hepatitis A disease dan vaccine is required to support such program for eradication of Hepatitis A. The aims of this study was to measure the knowledge of Indonesian community about hepatitis A disease and its vaccine indicated from knowledge score of correct answer towards questionnaire, as well as to analyze the factors that can influence it indicated from difference of mean of knowledge scores among groups of respondents characteristics. This study used an observational survey research design applying a cross-sectional multi-center approach. The number of sample was 500 respondents located in 5 provinces in Indonesia, namely DIY, Lampung, West Java, Central Kalimantan, and Central Sulawesi. Data collection was carried out using a questionnaire that was modified from the questionnaire in a similar previous study. The results showed that public knowledge related to diseases and hepatitis A vaccine in Indonesia was considered sufficient with the mean score obtained was 75.2% ± 12.2%. Statistical analysis using Mann-Whitney test showed that there were significant differences in score of knowledge between groups on the characteristics of experience of hearing a disease (p=0,000), experience of hearing a vaccine (p=0,000) and the experience of the child being vaccinated (p=0,000). There are 2 items of knowledge that werelack understood by respondents, namely treatment of hepatitis A that cannot be treated with antibiotics and immunizations and hepatitis A is not included yet in the national immunization program in Indonesia. It is concluded that community knowledge regarding hepatitis A disease and vaccine was fair (mean knowledge score between 65 – 80%). However, the government still needs to conduct educational programs for the Indonesian community about disease prevention through the vaccination process and provide counseling about the types of vaccines that are not included in the national health insurance program in Indonesia.